2012
DOI: 10.1039/c1cp22007a
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “HCl adsorption on ice at low temperature: a combined X-ray absorption, photoemission and infrared study” by P. Parent, J. Lasne, G. Marcotte and C. Laffon, Phys. Chem. Chem. Phys., 2011,13, 7142

Abstract: On the basis of NEXAFS, photoemission and FTIR spectra of ice films with low doses of adsorbed HCl, the authors of the PCCP paper "HCl adsorption on ice at low temperature: a combined X-ray absorption, photoemission and infrared study", Phys. Chem. Chem. Phys., 2011, 13, 7142, have come to conclusions regarding the behavior of submonolayer amounts of HCl at 50 K that contradict published results of the authors of this Comment. Our purpose is to argue that the conclusion, attributed going forward to PLML (autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 13 publications
2
17
0
1
Order By: Relevance
“…A possible attribution of the high BE feature to carbon-Cl compounds appears unlikely due to the low atomic ratio of carbon to chlorine (<0.1) as detected by XPS. The finding of molecular HCl cannot be explained by beam induced reactions either, , as radiation does not drive Cl – ions to reform HCl molecules. Consequently, these measurements provide direct spectroscopic evidence of the presence of molecular HCl and ionic Cl – upon adsorption with an average ratio of about 1:1 within the upper few nanometers of the ice sample, corresponding to a probing depth of ∼1.4 nm of these measurements with an electron kinetic energy of 274 eV.…”
mentioning
confidence: 93%
“…A possible attribution of the high BE feature to carbon-Cl compounds appears unlikely due to the low atomic ratio of carbon to chlorine (<0.1) as detected by XPS. The finding of molecular HCl cannot be explained by beam induced reactions either, , as radiation does not drive Cl – ions to reform HCl molecules. Consequently, these measurements provide direct spectroscopic evidence of the presence of molecular HCl and ionic Cl – upon adsorption with an average ratio of about 1:1 within the upper few nanometers of the ice sample, corresponding to a probing depth of ∼1.4 nm of these measurements with an electron kinetic energy of 274 eV.…”
mentioning
confidence: 93%
“…Kang et al ( 28 ), using Cs + reactive ion scattering and secondary ion mass spectrometry, and Devlin et al ( 2 ), using Fourier transform IR spectroscopic techniques, proposed that no ionization takes place below 50 K, whereas on increasing temperature, the rate of ionization was found to increase: from ~15% at 60 K to almost complete ionization taking place at 90 to 95 K. In contrast, Parent and Laffon ( 29 ) reported an ionization rate of 80% even at temperatures of 20 K. In a succeeding study ( 31 ), 92% ionization of HCl was reported at 50 K. These ionization rates were found to be independent of temperature, as they were similar for 50 and 90 K, supporting the theoretical prediction that HCl dissociation on ice surfaces is a barrierless process ( 19 ). These results gave rise to a controversial discussion on the rate of HCl ionization on ice surfaces ( 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the effect of temperature on acid dissociation was investigated at ice surfaces. These studies reported a wide range of observations from complete dissociation of HCl to a substantial portion of molecular HCl adsorption at the surface of ice at low temperature. Ayotte and coworkers studied the dissociation of hydrogen halides in ASW with reflection absorption infrared spectroscopy (RAIRS) and theoretical computations and reported , that HF behaves like a strong acid at cryogenic temperatures with its extensive ionic dissociation. It was suggested that the strong Zundel absorption is generated by a broad distribution of proton-shared complexes and hydrated proton CIP structures.…”
Section: Introductionmentioning
confidence: 99%
“…They interpreted the continuum band as signatures of polarizable hydrogen bonds of protonated water and acid–water cluster structures. The dissociation of acids in ice or ASW was also studied. Such studies have relevance in investigations of atmospheric heterogeneous reactions of acids occurring in ice particles in the upper atmosphere. Also, the studies may provide useful information regarding corresponding processes in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%